(untitled) (The International Journal for Scientific Research, 2023)
The research dealt with the problem of the armed conflict, and its impact on the Libyan society, in terms of studying the concept of armed conflict and its social and human repercussions in civil life and in terms of demographic and life transition. This research will also focus on the national responsibility to reduce armed conflicts, and how it is possible to advance society in the post-armed conflict stage, re-development, and reconstruction, and address all repercussions at the general level, as most Libyan cities witnessed the consequences of armed conflicts, including devastation, destruction, killing, and forced demographic movement. Not to mention the many negative results, such as the increase in cases of violence and terror among the various human groups, which requires the adoption of social programs and policies. In order to achieve an end to conflicts and achieve stability, and to reach sustainable solutions that address the armed conflict and reduce its societal repercussions.